The Colonial Heritage: Objects from the Pacific in a German Museum - Walda-Mandel, Stephanie (Pacific Geographies, 2019)
Ethnological museums in Germany, with their entanglements of colonial history and the not always unproblematic emergence of their collections, have not only become the focus of the public since the media attention on the Humboldt Forum in Berlin: long before that they have been critizised for their neglect in addressing the colonial heritage of their collections and the lack of information on the origins of the objects. This background also applies to many of the estimated 250,000 Oceanic objects (Buschmann 2018: 198) that are stored in German museums today, which will be the focus of this article. Since the beginning of these discussions and in provenance research of ethnological museums it has mainly been the Africa collections that were at the center of attention; more and more the territories in the Pacific and the collections stemming from German colonial territories in the Pacific are now being explored.